2017
DOI: 10.1088/1757-899x/257/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of pillar-shaped intermetallic compounds dispersed lead-free solder joint

Abstract: Abstract. Large area joining between a substrate and a heat sink is desirable for high performance power modules. An intermetallic compounds (IMCs) pillar dispersed solder joint has been developed as a highly durable joint to achieve large area joining. The aim of this study is to clarify the generation and growth mechanism of the IMC pillar during soldering process. The structural characteristic of the IMC pillar was also examined by cross-sectional observation. The area ratio of the IMC pillars in the cross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In a power module that is required larger area bonding compared to general electronic components, suppression of crack growth in a solder joint is effective to improve the reliability of the joint. The authors have developed the solder joint with pillar-shaped intermetallic compounds (IMC) for automotive applications to suppress the progress of the crack [2][3][4]. In the previous study, the effect of bonding conditions on the formation of pillar-shaped Cu-Sn IMCs was researched with several lead-free solder [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a power module that is required larger area bonding compared to general electronic components, suppression of crack growth in a solder joint is effective to improve the reliability of the joint. The authors have developed the solder joint with pillar-shaped intermetallic compounds (IMC) for automotive applications to suppress the progress of the crack [2][3][4]. In the previous study, the effect of bonding conditions on the formation of pillar-shaped Cu-Sn IMCs was researched with several lead-free solder [2].…”
Section: Introductionmentioning
confidence: 99%
“…The authors have developed the solder joint with pillar-shaped intermetallic compounds (IMC) for automotive applications to suppress the progress of the crack [2][3][4]. In the previous study, the effect of bonding conditions on the formation of pillar-shaped Cu-Sn IMCs was researched with several lead-free solder [2]. As a result, it was clarified that Sn-Ag-Cu-In solder forms a large quantity of pillar-shaped IMCs in the joint with Cu and the joint has excellent shear strength.…”
Section: Introductionmentioning
confidence: 99%
“…As the pillar shaped IMCs, Cu 6 Sn 5 is formed in the joint with Sn-3.0Ag-0.5Cu (SAC305), (Cu,Ni) 6 Sn 5 is done in the joint with a Ni plated electrode, and Cu 6 (Sn,In) 5 is formed in the joint with solder including In [4]. It has been revealed that the formation amount of pillar shaped IMCs depends on the temperature, and they are 3.5% and 5.5% at the joining temperature of 300°C and 330°C, respectively [5]. The aim of this study is to investigate the mechanical characteristics and thermal fatigue durability of the solder layer formed pillar shaped IMCs.…”
Section: Introductionmentioning
confidence: 99%